Pengaruh digital financial literacy, peer influence, self-control, dan lifestyle pada saving behavior generasi z penggemar k-pop di pulau jawa - Naswa Marsha Azzara; Yuyun Isbanah; Nadia Asandimitra Haryono; Ina Uswatun Nihaya (Jurnal Ilmu Manajemen, 2026)
This study aims to analyze the influence of digital financial literacy, peer influence, self-control, and lifestyle on the saving behavior of Generation Z K-Pop fans in Java. The research method used is quantitative with a correlational approach. The research population is Generation Z K-Pop fans in Java, with sampling using non-probability snowball sampling. Data was collected through an online questionnaire and 220 respondents who met the research criteria were obtained. Data analysis was performed using the Structural Equation Modeling (SEM) method with the help of SmartPLS software version 4.1.1.4. The results showed that digital financial literacy and peer influence did not affect on saving behavior. Meanwhile, self-control and lifestyle had a positive and significant effect on the saving behaviour of Generation Z K-Pop fans in Java. This study contributes by explaining saving behavior within fandom-based consumption contexts, where financial decisions are driven by both emotional attachment and planned saving strategies. The practical implications emphasize the importance of continuous and inclusive financial education initiatives led by regulators, alongside improved accessibility and quality of banking services to support effective financial management. Additionally, the findings suggest the K-pop industry can contribute by providing secure, flexible payment features that encourage responsible financial planning, thereby helping individuals minimize financial risks and make more structured spending decisions.